Proses pengeluaran hakmilik sambungan selepas pengambilan tanah - Syed Nasir, Syed Norul Shahril (2016)
The vigorous development nowadays depends on the needs of potential of land and Land Acquisition Act 1960 to be used in acquiring these lands. Land Acquisition Act 1960 is a law that regulates the acquisition of land starting from the application of agencies acquirer up to produce title in continuation. However, most agencies consider making land acquisition has been completed after the Form K endorsed by the land administration. Therefore, this study was conducted to identify the procedure of title in continuation after land acquisition which is the last process in the procedure of land acquisition. The research method focused on the theoretical research on the production process of title in continuation after the land acquisition. The study was conducted on respondents who worked in the Segamat Land Office through the interview method. The study found that the delay in issuance of title in continuation after land acquisition. Studies have identified factors that delay and improvement measures to overcome the problem. Department of Director General of Lands and Mines, the Director of State Lands and Mines, district land offices and agencies acquirer shall coordinate with each other to ensure the production process of title in continuation after land acquisition are implemented perfectly and set a time frame production. Thus, the results of this study can be used as a guide and basis for the parties responsible for improving and strengthening the land administration system in the process of land acquisition.